2002
DOI: 10.1046/j.1439-0418.2002.00622.x
|View full text |Cite
|
Sign up to set email alerts
|

Cotton pests and their natural enemies in Madagascar

Abstract: An update on the cotton pest complex and its associated natural enemies in Madagascar is provided. Since the end of the 1970s, when the previous reports had been published, the population dynamics of the principal pests in Malagasy cotton have undergone considerable changes. The American bollworm Helicoverpa armigera Hübner (Lep., Noctuidae) is still a limiting factor for production and can be considered the key pest, whereas the Egyptian leaf worm Spodoptera littoralis Boisduval (Lep., Noctuidae) and the cott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…If these compounds are to realize their potential in applied entomology, more studies need to be conducted using HIPVs that study the response of natural enemies under Þeld conditions. A rich diversity of parasitoid and arthropod predator species is known to inhabit cotton Þelds (Kuklinski andBorgemeister 2002, Boyd et al 2005), and it is generally recognized that natural enemies play an important role in regulating pest herbivore populations (King et al 1985, Hopper et al1991. In particular, the predator community in cotton Þelds was found to be shaped chießy by species that were abundant in these regions, including Orius similes Zheng and Propylaea japonica Thunberg (Li et al 2003).…”
mentioning
confidence: 99%
“…If these compounds are to realize their potential in applied entomology, more studies need to be conducted using HIPVs that study the response of natural enemies under Þeld conditions. A rich diversity of parasitoid and arthropod predator species is known to inhabit cotton Þelds (Kuklinski andBorgemeister 2002, Boyd et al 2005), and it is generally recognized that natural enemies play an important role in regulating pest herbivore populations (King et al 1985, Hopper et al1991. In particular, the predator community in cotton Þelds was found to be shaped chießy by species that were abundant in these regions, including Orius similes Zheng and Propylaea japonica Thunberg (Li et al 2003).…”
mentioning
confidence: 99%
“…In the diet, we found Noctuid pest species of major agricultural importance such as Earias cupreoviridis, which damaged cotton fields in Tanzania and Uganda [84]. Anomis flava is another Noctuid pest that we detected in this study and has been reported to damage cotton in Australia, the Philippines, India, and Madagascar [85][86][87]. Sphingomorpha chlorea (a widespread noctuid) was found to cause considerable damage to fruits in Southeast Asia and Africa [88].…”
Section: Pest Arthropods In the Diet Of Batsmentioning
confidence: 93%
“…A broad complex of natural enemies act against H. armigera in various agro-ecosystems worldwide (Stam and Elmosa 1990;Kuklinski and Borgemeister 2002). Parasitoids seem to be especially efficient natural enemies, and have been reported to cause mortality levels up to 50% of Heliothis spp.…”
Section: Introductionmentioning
confidence: 99%